Worker Mobility and Domestic Production Networks - Cardoza, Marvin (IMF Working Papers; Working Paper ;, 2020)
We show that domestic production networks shape worker flows between firms. Data on the universe of firm-to-firm transactions for the Dominican Republic, matched with employer-employee records, reveals that about 20 percent of workers who change firms move to a buyer or supplier of their original firm. This is a considerably larger share than would be implied by a random allocation of movers to firms. We find considerable gains associated with this form of hiring: higher worker wages, lower job separation rates, faster firm productivity growth, and faster coworker wage growth. Hiring workers from a supplier is followed by a rising share of purchases from that supplier. These findings indicate that human capital is easily transferable along the supply chain and that human capital accumulated while working at a firm is complementary with the intermediate products/services produced by that firm.